Naissance et mutations d’un marché éditorial : les manuels du supérieur - Jean-Yves Mollier (Revue d’Histoire des Sciences Humaines)
Although University textbooks eventually became important in France after 1960, they lack the historical capital of the British Companions, which appeared a century earlier. The pecia tradition, of course, dates back to the Middle Ages and preceded the invention of print, but it then concerned only scholars, not the huge post-baccalaureate student audience of over two million individuals, according to present estimations. The present day University textbook in France is closer and closer in its style to the “high school” textbook, which borrowed from the “primary school” one. Before it came to the fore with “U”, then “Cursus” and “Carré H” and began to flourish, to proliferate, with several specialized publishers, there were a number of series like “Que Sais-je?”, “Kiosque” or “10-18”. This article attempts to present an archeology of the phenomenon, analyzes its growth and its mutations from one century to the next, and then, so as to underscore the peculiarities of French-style textbooks, draws comparisons with British, German and American practices.